KIẾN THỨC VÀ THỰC HÀNH TRONG ĐIỀU TRỊ TĂNG HUYẾT ÁP CỦA NGƯỜI BỆNH NGOẠI TRÚ TẠI BỆNH VIỆN ĐA KHOA XANH PÔN NĂM 2022 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the knowledge and practices related to hypertension management among outpatients at Saint Paul General Hospital in 2022.Methods: A cross-sectional descriptive study was conducted on 96 patients diagnosed with hypertension from February to May 2022 at the Outpatient Department of Saint Paul General Hospital.Results: The proportion of patients with adequate knowledge of hypertension management was 73.95%, while 63.5% demonstrated adequate practices. Although patients had good knowledge in several areas, some aspects remained limited, including maintaining a healthy weight and avoiding overweight/obesity (54.17%) and engaging in moderate physical labor (46.88%). Several practices were suboptimal, such as regular health check-ups every less than three months (36.46%), daily blood pressure monitoring (16.67%), exclusive use of vegetable oil (58.33%), engaging in physical exercise for 30–60 minutes per day (56.25%), and appropriate management of sudden blood pressure elevation (56.25%).Conclusion: The study found that 73.95% of patients had adequate knowledge and 63.5% had adequate practices regarding hypertension management. Patients still had limited knowledge regarding weight control and physical activity. A gap between knowledge and practice persists, with some patients showing inadequate behaviors in blood pressure monitoring, regular health check-ups, maintaining a healthy lifestyle, and managing sudden hypertension episodes. Therefore, health education interventions are needed to improve areas where patients’ knowledge and practices remain insufficient.
Keywords: knowledge, practice, hypertension management, hypertension